Low Carbon Readiness Index: A short measure to predict private low carbon behaviour. (June 2018) - O'Brien, Léan V.; Meis, Julia; Anderson, Rebekah C.; Rizio, Stephanie M.; Ambrose, Michael; Bruce, Gordana; Critchley, Christine R.; Dudgeon, Paul; Newton, Peter; Robins, Garry; Kashima, Yoshihisa
Abstract: This paper presents a theoretical argument that low carbon strivings – personal goals to reduce carbon footprint in the household – can predict a wide range of diverse behaviours to reduce greenhouse gas emissions, and reports four studies to validate Low Carbon Readiness Index (LCRI), a short, three-item measure of low carbon strivings. It is a simple and easy-to-use indicator of the general public's readiness to transition to a fully low carbon lifestyle. LCRI is associated with validated measures predicting environmentally significant reported behaviour (Study 1), multiple low carbon behavioural clusters (Study 2 & 3), and predicts reduction in actual energy use, arguably an aggregate measure of actual low carbon behaviours (Study 4). LCRI can be used to develop low carbon policies and monitor their implementation. Highlights: Low Carbon Readiness Index (LCRI) is a three-item measure of low carbon strivings. LCRI predicts reported low carbon behaviours, and reduction in actual energy use. LCRI can be used to develop low carbon policies and monitor their implementation.